(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Vitamin D deficiency and anemia are conditions commonly in eldery. Both result in significant morbidity in eldery. Relationship between 25-hydroxyvitamin D and anemia need to be concern, particularly in the elderly. including those characterized by inflammatory processes. The aim of this study is to analyze association and differentiations between of 25-hydroxyvitamin D levels and anemia parameters in elderly with anemia inflammation and non-inflammation. Methods: An observational study, at Posyandu Lansia Puskesmas Sokaraja, was conducted among 40 subjects aged ≥60 years consecutively, between September - November 2015. 25-Hydroxyvitamin D, hemoglobin levels, hematocrit and red blood cell counts were measured. 25-Hydroxyvitamin D deficiency defined in level <30 ng/mL and anemia defined by the World Health Organization. Results: After adjustment for CRP levels and leucocyte count, 25-Hydroxyvitamin D was inversely associated with anemia inflammation (p=0,018; p=0,010; p=0,000)and non-inflammation (p= 0,002; p=0,002; p=0,000). There was significantly differences 25-hydroxyvitamin D levels (p = 0.003) in elderly with anemia of inflammation and non-inflammation. Conclusion: 25-Hydroxyvitamin D levels was associated with anemia inflammation and non-inflammation in eldery. Vitamin D may suppress inflammatory mechanism, and studies to determine whether chronic disease involves anemia inflamation are warranted. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.302-306